[Rezension von: The Oxford handbook of Christianity and law] - Phillips, Anthony (Journal of Anglican studies, 2025)
John Witte Jr. and Rafael Domingo, The Oxford Handbook of Christianity and Law (Oxford: Oxford University Press, 2024) HB xviii + 899 pp. £132.50/$205.00 ISBN 9780197606759 - Volume 23 Issue 1